The Vacuolar-Type H+-ATPase in Ovine Rumen Epithelium is Regulated by Metabolic Signals. (1st December 2009) - Kuzinski, Judith; Zitnan, Rudolf; Warnke-Gurgel, Christina; Schweigel, Monika
Abstract : In this study, the effect of metabolic inhibition (MI) by glucose substitution with 2-deoxyglucose (2-DOG) and/or application of antimycin A on ovine rumen epithelial cells (REC) vacuolar-typeH + -ATPase (vH + -ATPase) activity was investigated. Using fluorescent spectroscopy, basalpH i of REC was measured to be7.3 ± 0.1 inHCO 3 − -free, glucose-containing NaCl medium. MI induced a strongpH i reduction (− 0.44 ± 0.04 pH units) with a more pronounced effect of 2-DOG compared to antimycin A (− 0.30 ± 0.03 versus− 0.21 ± 0.03 pH units). Treatment with foliomycin, a specific vH + -ATPase inhibitor, decreased RECpH i by0.21 ± 0.05 pH units. After MI induction, this effect was nearly abolished (− 0.03 ± 0.02 pH units). In addition, membrane-associated localization of vH + -ATPase B subunit disappeared. Metabolic control of vH + -ATPase involving regulation of its assembly state by elements of the glycolytic pathway could provide a means to adapt REC ATP consumption according to energy availability.